Prevalence of schizophrenia in patients with psoriasis: a nationwide study - Hung-Pin Tu; Chu-Ling Yu; Cheng-Che E. Lan; Sebastian Yu (Wolters Kluwer Medknow Publications, 2017)
Background/Objective: The prevalence of selected psychiatric disorders, such as depression and anxiety, is higher in patients with psoriasis. However, the association between psoriasis and schizophrenia is less clear. Here, we investigated whether the prevalence of schizophrenia is higher in patients with psoriasis. Methods: In this cross-sectional study, we analyzed the 1-million-person cohort enrolled from Taiwan's National Health Insurance Research Database. Psoriasis, schizophrenia, and comorbidities were ascertained by the International Classification of Diseases, 9th revision, Clinical Modification coding. For schizophrenia, the concomitant catastrophic illness certificate was used to verify the diagnosis. The prevalence of schizophrenia in patients with psoriasis was compared with the prevalence of schizophrenia in a comparable population using a generalized linear mixed model. Results: The prevalence of schizophrenia was significantly higher in patients with psoriasis than in the comparison population [prevalence ratio = 1.77, 95% confidence interval (CI) = 1.48-2.12, p < 0.0001)]. Within the psoriasis cohort, patients aged between 40 years and 59 years had a higher odds ratio (OR) for schizophrenia (OR = 2.49, 95% CI = 1.55-4.00, p = 0.0002). Furthermore, psoriatic patients with comorbid cerebrovascular disease (OR = 2.01, 95% CI = 1.11-3.65, p = 0.0220) and chronic pulmonary disease (OR = 1.64, 95% CI = 1.07-2.49, p = 0.0218) had higher odds for schizophrenia. Conclusion: Schizophrenia is more prevalent in patients with psoriasis. Although the exact mechanisms remain to be clarified, the finding that psoriatic patients with comorbid cerebrovascular disease or chronic pulmonary disease have higher odds for schizophrenia may imply psoriatic patients with those comorbidities are likely to have higher inflammatory burden, which would contribute to the development of schizophrenia if a disruption of the blood-brain barrier is present. Further investigations are indicated to validate the hypothesis explaining the association between known comorbidies of psoriasis and schizophrenia.